Assessment of Clinical Pro?le of Patients with Allergic Rhinitis - Monika Sharma; KM Jameel (Asian Journal of Medical Research, 2021)
Background: Assessing clinical profile of patients with Allergic rhinitis (AR). Subjects & Methods: One hundred forty- eight patients compris- ing of 80 males and 68 females of AR were included in the study. Clinical symptoms were recorded. Results: Common symptoms were running nose seen in 125 (84.4%), nasal blockage in 110 (74.4%), sneezing in 97 (65.5%), nasal itching in 80 (54%) and watery eyes in 72 (48.6%) cases. Mild intermittent cases were seen in 17%, moderate/ severe intermittent in 30%, mild persistent in 25% and moderate/ severe persistent in 28%. Allergens found to be tobacco smoke in 18%, animals in 20%, pollen in 36% and dust in 26%. A significant difference was seen (P< 0.05). Conclusion: Maximum cases were seen in males and age group 31-40 years in both genders. Pollens were most common allergens.